Evaluation of urodynamic parameters after sling surgery in men with post-prostatectomy urinary incontinence - Paiva,Odair Gomes (2018)
ABSTRACT Objective: To evaluate urodynamic alterations after sub-urethral sling surgery (SSU) in patients with post-prostatectomy urinary incontinence (PPUI). Materials and Methods: We evaluated data of 22 patients submitted to radical prosta- tectomy (RP) or transurethral resection of prostate (TURP) that presented post-surgical urinary incontinence and were treated with SSU implant in a pilot study previously performed in our institution. Methods: Those patients with PPUI were evaluated by urodynamic exam (UD) before and after surgery, and the parameters were compared, including uroflow, cystometry and micturition study. Exclusion criteria included patients without pre-operatory urodynamic study, those with urethral stenosis, those not healed of prostate cancer, pa- tients without clinical conditions to be submitted to urodynamic study and those with severe neurological diseases or that refused to sign the consent form. Results were analyzed statistically by Fisher, Wilcoxon or Mann-Whitney tests. Results: During free uroflow, none parameters showed any statistical significant differ- ences. During cystometry, there were also no statistical differences and the same was observed at pressure versus flow study; the exception was at maximal flow detrusor pressure (PdetQmax), that was lower at post-operatory (p=0.028). In relation to the presence of urinary dysfunctions associated to PPUI, we observed a significant reduc- tion of detrusor overactivity (p=0.035) in relation to pre-operatory period. Conclusion: SSU surgery significantly reduced detrusor overactivity and PdetQMax; however, there were no alterations of other evaluated urodynamic parameters.